Wyzwania reformy samorządowej i procesu decentralizacji na Ukrainie po 1991 roku - Czachor, Rafał (Przegląd Wschodnioeuropejski, 2019)
Local self-government reforms were one of most important elements of political transformations in the post-communist countries. Currently Ukrainian authorities pay much attention to this problem, however all previous attempts of reforms were insufficient. The paper deals with theoretical aspects of local self-government models in a functional approach and discusses challenges that Ukraine will face during the reform. The author concludes that despite of positive tendencies of the reform, it brings serious threats to Ukrainian statehood.